Integration of microRNA and mRNA analyses depicts the potential roles of Momordica charantia saponin administration in insulin resistance of juvenile common carp (Cyprinus carpio) fed with a high-starch diet - Fan, Ze; Wang, Liansheng; Li, Chenhui; Wu, Di; Li, Jinnan; Zhang, Haitao; Xiong, Siwei; Miao, Linghong; Ge, Xianping; Li, Zhengwei (Frontiers in Molecular Biosciences, 2023)
Bacground: The regulation of target gene mRNA mediated by microRNA may play an important role in glucose metabolism in fish. Previous research findings in our research group revealed that Momordica charantia saponins (MS) administration in a high-starch diet could improve insulin resistance of common carp through renovating insulin signaling pathways, of which the fundamental mechanism have remained unknown by far. To reveal this potential mechanism, we aimed to investigate the difference of miRNA and mRNA expression profiles between common carp fed with high-stach diets containing MS (HS_MS1 and HS_MS2) and common carp fed with high-starch diets (HS). Results: Thorugh miRNA deep-sequencing, 10 significantly differentially expressed miRNAs in HC and HC_MS1, including 1 upregulated and 9 downregulated miRNAs, whereas 11 significantly differentially expressed miRNAs in HC and HC_MS2, including 4 upregulated and 6 downregulated miRNAs. These miRNAs may not only be involved in the regulation of insulin signaling pathway and insulin resistance in common carp, but also be the markers in liver of MS therapy for remission of insulin resistance. This study identified ten potential known miRNAs including ccr-miR-10b, ccr-miR-122, ccr-miR-143, ccr-miR-146a, ccr-miR-155, ccr-miR-16c, ccr-miR-200a, ccr-miR-29a, ccr-miR-34 and ccr-miR-375, as candidates participating in modulating the liver insulin resistance. According to the biopathway enrichment analysis of the 252 target genes using KEGG classical biopathway database, the relative expression levels of gsk3bb, pik3r1 and pik3r3b were analyzed using RNA-seq. compared to the HC group, siginificant decrease in the relative expression levels of pik3r1 and pik3r3b were observed in HC_MS1 and HC_MS2 groups (P<0.05). This study raised a presumption of the presence of ccr-miR-29a targeting pik3r1 or ccr-miR-143 targeting pik3r3 with likely roles in Momordica charantia saponins remmiting the liver insulin resistance. Conclusion: The findings will further deepen the understanding of carbohydrate metabolism of commn carp and provide important scientific basis for the application of momordica saponins as functional nutrients to alleviate insulin resistance of fish in fish culture.